REACTOR CAVITY COOLING SYSTEM WITH PASSIVE SAFETY FEATURES ON RDE: THERMAL ANALYSIS DURING ACCIDENT - Rahayu Kusumastuti; Sriyono Sriyono; Mulya Juarsa; Hendro Tjahjono; I. D. Irianto; Topan Setiadipura; D. H. Salimy; A. Hafid (JURNAL TEKNOLOGI REAKTOR NUKLIR TRI DASA MEGA, 2019)
Reaktor Daya Eksperimental (RDE) is an experimental power reactor based on HTGR technology that implements inherent safety system. Its safety systems are in compliance with “defense in depth” philosophy. RDE is also equipped with reactor cavity cooling system (RCCS) used to remove the heat transferred from the reactor vessel to the containment structure. The RCCS is designed to fulfil this role by maintain the reactor vessel under the maximum allowable temperature during normal operation and protecting the containment structure in the event of failure of all passive cooling systems. The performance and reliability of the RCCS, therefore, are considered as critical factors in determining maximum design power level related to heat removal. RCCS for RDE will use a novel shape to efficiently remove the heat released from the RPV through thermal radiation and natural convection. This paper discusses the calculation of RCCS thermal analysis during accident. The RPV temperature must be maintained below 65ºC. The accident is assumed that there is no electricity from diesel generator supplied to the blower. The methodology used is based on the calculation of mathematical model of the RCCS in the passive mode. The heat is released through cavity by natural convection, in which the RCCS is capable to withdraw the heat at the rate of 50.54 kW per hour.Keywords: Passive safety, RCCS, RDE, Thermal analysis